2007
DOI: 10.1259/bjr/32814323
|View full text |Cite|
|
Sign up to set email alerts
|

Doses to critical organs following radiotherapy and concomitant imaging of the larynx and breast

Abstract: The development of conformal radiotherapy carries with it the implication of an increased number of imaging procedures at various stages throughout the overall treatment, principally for verification at some, or all, of the treatment fractions. This raises the issue of the balance between the benefit of these additional imaging exposures and the associated risk of radiocarcinogenesis arising from them. As such, it is necessary to appreciate the doses to critical organs for which individual carcinogenic risks h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…The use of CBCT to improve the setup accuracy in breast RT can increase dose to organs at risk significantly, 15,[33][34][35] and potentially increasing the patients' likelihood of developing a secondary cancer. 36 The associated imaging dose and risks should be carefully considered before use of CBCT for breast especially now that we have identified no statistically significant benefit with CBCT-B use.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CBCT to improve the setup accuracy in breast RT can increase dose to organs at risk significantly, 15,[33][34][35] and potentially increasing the patients' likelihood of developing a secondary cancer. 36 The associated imaging dose and risks should be carefully considered before use of CBCT for breast especially now that we have identified no statistically significant benefit with CBCT-B use.…”
Section: Discussionmentioning
confidence: 99%
“…Daily volumetric imaging has been shown to be effective in reducing systematic and random uncertainties in patient positioning for various tumour sites [1][2][3] and improved dose delivery. 4,5 Volumetric imaging may offer additional information to improve the setup accuracy in breast radiotherapy; [6][7][8] however, daily imaging with ionising radiation can increase the dose to organs at risk (OAR) significantly, [9][10][11] potentially increasing the patients' likelihood of developing a secondary cancer. 12 Numerous studies have reported the dose to OAR from various image guidance procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] . The contributions of IGRT to non-target organ doses have been put into context by Harrison et al [28][29][30] who showed that intense IGRT imaging procedures contributed 5 -30% of the total dose to non-target organs with the remainder dose from the radiotherapy scattered and leakage radiation. Harrison et al expressed reluctance to assign risk estimates to their measured organ doses although, other groups have found the risk models useful to compare different treatment methods whilst accepting the large uncertainties in an absolute risk value.…”
mentioning
confidence: 99%